Development of a dimer-based screening system for dimerization inhibitor of HIV-1 protease - I Dewa Agung Panji Dwipayana; Yana Maolana Syah; Reza Aditama; Feraliana Feraliana; Azzania Fibriani (Microbiology Division, Research Center for Biology, Indonesian Institute of Sciences, 2020)
An in vitro dimer-based screening system (DBSS) for selecting new HIV-1 protease dimerization inhibitor candidates from natural compounds had been established. This system utilizes a fusion between HIV-1 protease and dimer binding domain of AraC protein (proteaseHIV1-AraCDBD) where fluorescence signal will be emitted in the presence of HIV-1 protease inhibitor. However, this screening system had not been evaluated. Therefore, this study was aimed to evaluate it in recombinant Escherichia coli culture. The expression of proteaseHIV1-AraCDBD fusion gene was observed for 18 hours. Its crude lysate isolation was done once every 3 hours and analyzed using SDS PAGE. To test the DBSS, darunavir was used as positive control, and Nigella sativa extract (JH3) was used as the test compound. The results of SDS PAGE analysis on crude lysates presented a 24.2 kDa band, which was the predicted size of the proteaseHIV1-AraCDBD fusion protein based on its amino acid sequence. The growth curve and protein expression profiles revealed that the 15 hours was the optimum culture age to be used in the screening system. Darunavir testing in DBSS showed an increase in fluorescence signal compared to the negative control. The same increase in fluorescence signal was also obtained from the JH3 compound test. In conclusion, DBSS could be used as an assay to screen for new HIV-1 protease inhibitors, and the JH3 compound demonstrated the ability to inhibit HIV-1 protease dimerization.